2018
DOI: 10.1007/s40093-018-0215-9
|View full text |Cite
|
Sign up to set email alerts
|

Availability and dynamics of organic carbon and nitrogen indices in some soils amended with animal manures and ashes

Abstract: Purpose The study evaluated dried manures and manure ashes as alternative products from animal manures, and determined the dynamics of soil nitrogen availability indices and organic carbon release in some soils amended with dried manures and ashes under laboratory incubation, screen-house and field experiments. Methods Cattle, goat and poultry manures were collected and air dried to produce dried manures after which part of the dried manures were burnt in open space at a temperature range of 320-450 °C to prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…The authors also highlighted that the organic carbon content was smaller the longer the experiment lasted (regardless of the fluctuations in some sampling dates). Opposite results were presented by Olowoboko et al [58]. The authors, after conducting an 8-week incubation experiment, found that the addition of dried manure (cattle, goat, and chicken), ash from these materials, and mineral fertilization with NPK, as a rule, led to an increase in organic carbon content, in comparison to the control treatment (without additives).…”
Section: Total Organic Carbon Contentmentioning
confidence: 85%
“…The authors also highlighted that the organic carbon content was smaller the longer the experiment lasted (regardless of the fluctuations in some sampling dates). Opposite results were presented by Olowoboko et al [58]. The authors, after conducting an 8-week incubation experiment, found that the addition of dried manure (cattle, goat, and chicken), ash from these materials, and mineral fertilization with NPK, as a rule, led to an increase in organic carbon content, in comparison to the control treatment (without additives).…”
Section: Total Organic Carbon Contentmentioning
confidence: 85%
“…During the decomposition of manure, the N that is readily available and abundant stimulates the mineralization of soil N (Tracy & Frank, 1998). In addition, manure can increase soil organic N content (Ma et al, 2020), which is mediated by microbial activities (Olowoboko et al, 2018), exerting a priming effect on SOM (Ma et al, 2020). The addition of crop residues and/or manure to the soil is considered an effective alternative that can act as a fertilizer, increasing SOM concentrations and improving the biological activity and nutrient availability in soil (Dubeux et al, 2009; Maia et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in stable SOC usually occur very slowly (over decades) and, therefore, changes in the organic carbon content of agricultural soils are small, being most often determined in the upper layers. Due to its stability over time, SOC can be an important factor influencing the actual sorption/desorption processes of different toxic metals in soil [43,44].…”
Section: Evaluation Of the Influence Of Factors On The Extraction Of ...mentioning
confidence: 99%
“…The desorption process involves selecting a distribution coefficient with the lowest value (high mobility) [47]. The characterization of Kd in the laboratory system and the extrapolation in the real environment can be difficult, mostly due to the complexity of the mechanisms involved in the sorption/desorption process [43].…”
Section: Evaluation Of the Influence Of Factors On The Extraction Of ...mentioning
confidence: 99%